Dinâmica das trocas de massa e energia em região de Cerrado na Baixada Cuiabana - Arruda, Paulo Henrique Zanella de (2014)
The Brazilian cerrado is the major savanna region in South America, and comprises about 22% of the entire national territory in Brazil, bordering four of the other five national biomes. However, the mass (carbon and water) and energy exchanges dynamics with the atmosphere are not well understood, especially in so-called Cerrado Campo Sujo. Therefore, this work was conducted to observe, evaluate and describe the seasonal dynamics in net CO2 ecosystem exchange with the atmosphere and the components of the energy balance in a representative area of Cerrado Campo Sujo on the Baixada Cuiabana, in Mato Grosso - Brazil. The study was conducted at the Fazenda Miranda (15º43 ' S and 56º04' W), where a micrometeorological tower equipped with an eddy covariance system was installed. The data presented here were collected and analyzed from March 2011 to December 2013, and allowed us to infer that the seasonal variations in the hydrological regime were the main regulatory component of the energy balance and net CO2 exchange with the atmosphere. In this period, the ecosystem showed a light source of carbon to atmosphere, but may behave as a sink due to the hydrological regime. This relationship can also be observed in seasonal data, with higher magnitudes in net CO2 exchange values during the rainy season, this behavior is similarly to semi-deciduous tropical forests. When the net CO2 ecosystem Exchange is partitioned, the ecossitem repiration tends to be greater in magnitude of the gross primary productivity in most period of the study. The components of the energy balance also shows seasonal variations in their behavior, with the average of latent heat flux twice high in the rainy season compared to dry season. The sensible heat flux is higher during the dry season, but with smaller magnitudes. The data presented are consistent with previous studies conducted in different areas of the Brazilian Cerrado and tropical savannas in other parts of the globe.